Artificial intelligence as a tool to practice and improve speaking and listening skills in English - REIS, Onezimo Vitor Matos (2024)
The main purpose of this study is to analyze the ways in which it is feasible to develop oral production and comprehension skills in English by using the Praktika artificial intelligence application. The methodology consists of reviewing the literature on artificial intelligence and oral production and comprehension skills. The research approach is qualitative, exploratory in nature, describing ways of improving English oral production and comprehension skills by using the artificial intelligence application. Three specific objectives were outlined: (1) to investigate the impact of artificial intelligence in the world; (2) to describe the skills of oral production and comprehension in English, based on the communicative approach; and (3) to analyze the Praktika application designed to improve oral communication skills. In order to achieve these goals, the article is based on theoretical contributions from authors such as Testa (2021); Edmett et al. (2023); Melo (2019); Richards (2006, 2008); Ludermir (2021); Almeida Filho (1998, 2009); Brown (2006); Harmer (1998); Rost (2015) and other researchers who have dedicated themselves intensively to studying this area. After the exploratory literature search, potential ways of improving learners' English oral production and comprehension skills were identified, such as conversation simulations, a variety of topics, pronunciation, and linguistic variation, feedback on oral communication skills, and other approaches.